The role of indole derivative in the growth of plants: A review - Sun, Ping; Huang, Yuanqin; Yang, Xiaoyan; Liao, Anjing; Wu, Jian (Frontiers in Plant Science, 2023)
Indole compounds with their unique properties of mimicking peptide structures and reversible binding to enzymes are of great exploitative value in the regulation of plant growth. They stimulate root and fruit formation and activate the plant’s immune system against biotic and abiotic factors harmful to the plant. Analysis of target recognition, receptor recognition, key activation sites and activation mechanisms of indoles in plants to enhance crop growth or disease resistance is a crucial step for further developing compounds as plant growth regulators and immune inducers. Therefore, this review focused on the mechanism of action of indoles in regulating plant growth and enhancing plant resistance to biotic and abiotic stresses.